Imperial visions : nationalist imagination and geographical expansion in the Russian Far East, 1840-1865 - Bassin, Mark (Cambridge studies in historical geography, 1999)
"In the middle of the nineteenth century, the Russian empire made a dramatic advance on the Pacific by annexing the vast regions of the Amur and Ussuri rivers. Within a decade of its acquisition, however, the dreams were gone and the Amur region was largely abandoned and forgotten. In an innovative examination of Russia's perceptions of the new territories in the Far East, Mark Bassin sets the Amur enigma squarely in the context of the Zeitgeist in Russia at the time. His argument is that the grand vision of Russia on the shores of the Pacific was intimately related to a number of major preoccupations of the day, including social reform, the search for samopoznanie or national self-understanding, Russia's relationship to the West, and the belief in a mission of universal salvation."--Jacket